Pemetaan Kerentanan Kebakaran Hutan di Pulau Buru, Provinsi Maluku Berdasarkan Fire Hotspot - Abdul Muin; Heinrich Rakuasa (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Buru Island is one of the areas in Maluku Province where forest fires are common. The prolonged summer season, flammable vegetation and the practice of clearing agricultural land and settlements by burning can also trigger forest fires on Buru Island. This research uses fire hotspots in 2019-2023 obtained from the Fire Information for Resource Management System (FIRMS) and analyzed using the Kernel Density method in Arc GIS software. The results showed that in 2019 there were 224 fire hotspots spread across Buru Island, in 2020 there were 30 fire hotspots, in 2021 there were 31 fire hotspots, in 2022 there were 31 fire hotspots, in 2022 there were 32 fire hotspots and in 2023 there were 23 hotspots spread across Buru Island. The results also show that the level of forest fire vulnerability in the very low vulnerability class has an area of 543,868.30 ha or 63.76%, low vulnerability class of 201,449.44 ha (23.62%), vulnerability class of 83,344.31 (9.77%), and high vulnerability class of 24,327.01 ha or 2.85% of the total area of Buru Island. The results of the study are expected to help the local government in future forest fire disaster mitigation efforts.